Legal Protection Of Welfare Teacher Assistant Garden Children - Kusti'ah Kusti'ah (Universitas Islam Sultan Agung, 2020)
The problems that arise in this research are: 1. What is the Realization of Legal Protection for Kindergarten Assistance Teachers' Welfare in Demak Regency, 2. What Barriers Arise in Protecting the Rights of Kindergarten Assistance Teachers in Demak Regency, 3 How is the Kindergarten Assistance Teacher Contract Completion after the employment contract ends.The method used in this research is qualitative descriptive with the research location in Demak Regency. Data sources use primary and secondary data. Respondents in this study were drawn by means of